#1**0 **

The above simplified is: 4y - x = 1

2y + x = 5

These 2 equations are in standard form. Let's use a method to solve it without changing them at all.

Add the 2 equations together, keeping the variables on the same side:

4y | -x | = | 1 |

+ (-2y) | + (-x) | = | + (-5) |

2y | + 0 | = | -4 |

Divide each side by 2, y = -2

Put the solution for y (-2) back into each equation. Then, solve for x.

If you had needed or wanted to, you could have multiplied the bottom equation by -2 to eliminate y, then solve for x. You can multiply both equations by numbers, as long as you remember to multiply both sides by that number.

helperid1839321
May 2, 2017